Recent Advances in Cereals, Legumes and Oilseeds Grain Products Rheology and Quality (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Special Issue presents information on the progress made in recent years in cereals’, legumes’, and oilseed grain products’ rheology and quality. This Special Issue capitalizes the experience of authors in grain processing for obtaining food products qualitatively improved based on the quality of raw materials used and applied technologies or intended for special nutrition, such as gluten-free one or with low sodium content. This Special Issue also presents some issues related to byproduct valorization through circular economy approaches obtained from the processing of different cereals and oilseeds grains and new methods for rapid assessment of bread quality.